Awareness of anaphylaxis among public in Al-Ahsa City of Saudi Arabia: A cross-sectional study. - Ahmed Alanazy; Raja Saad Boodai; Badiah Ibrahim Alhulaybi; Amenah Ibrahim Alraihan; Raghad Ahmed Almulhim; Bainah Fahad Almulhim; Suchithra K Rajappan; Abdullah Alruwaili; Ahmad Alanazi (PLoS ONE)
Background Anaphylaxis is a severe, life-threatening allergic reaction requiring prompt treatment with epinephrine. However, gaps in public understanding exist globally. To guide future education efforts, this study assessed anaphylaxis awareness among adults in Al-Ahsa, Saudi Arabia. Methods A cross-sectional survey assessed knowledge among 380 adults using a validated questionnaire. Convenience sampling was used with data collected via online platforms. Descriptive statistics were calculated, and associations were tested. We analyzed the data using SPSS software. Results Knowledge was suboptimal, with a mean score of 34.5/60. Most identified the anaphylaxis definition (76.1%) and rapid symptom onset (78.9% within minutes). But just 37.9% recognized epinephrine as a first-line treatment and only 17.4% had auto-injector training. Nearly half (48.4%) needed to learn the proper EpiPen injection site. Under half understood the need for long-term allergen avoidance. Older age, more education, and Job status were associated with higher scores. Conclusion This study reveals critical gaps in anaphylaxis knowledge among adults in Al-Ahsa, Saudi Arabia. Poor understanding of emergency treatment and long-term management highlights the urgent need for improved public awareness. Targeted educational initiatives must emphasize prompt epinephrine administration, proper auto-injector use, and allergen avoidance. Collaborative efforts engaging healthcare professionals, schools, and policymakers are essential to enhance anaphylaxis preparedness through focused training and tailored awareness campaigns. This will empower the Saudi public to recognize symptoms quickly and respond effectively, saving lives from this dangerous allergic reaction.